2019
DOI: 10.1002/jeab.575
|View full text |Cite
|
Sign up to set email alerts
|

Examining stimuli paired with alternative reinforcement to mitigate resurgence in children diagnosed with autism spectrum disorder and pigeons

Abstract: In two laboratory experiments, we examined whether stimuli paired with alternative reinforcers could mitigate resurgence of a previously reinforced target response with pigeons (Experiment 1) and children diagnosed with Autism Spectrum Disorder (Experiment 2). In Phase 1, we arranged food reinforcement according to a variable-ratio schedule for engaging in a target response. In Phase 2, we arranged extinction for target responding and differentially reinforced alternative responding according to a fixed-ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…Future research could evaluate reinforcement duration and its impact on resurgence. In addition, clinicians should use recent findings from studies seeking to mitigate resurgence in order to decrease its expected impact (e.g., Craig et al, 2017;Fisher et al, 2018;Fuhrman et al, 2016;Shvarts et al, 2020). Recently, published research has focused on different strategies for schedule thinning including providing alternative reinforcers while schedule thinning (Austin & Tiger, 2015) and using shaping during communication training (Ghaemmaghami et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Future research could evaluate reinforcement duration and its impact on resurgence. In addition, clinicians should use recent findings from studies seeking to mitigate resurgence in order to decrease its expected impact (e.g., Craig et al, 2017;Fisher et al, 2018;Fuhrman et al, 2016;Shvarts et al, 2020). Recently, published research has focused on different strategies for schedule thinning including providing alternative reinforcers while schedule thinning (Austin & Tiger, 2015) and using shaping during communication training (Ghaemmaghami et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the influence of proximity as a variable influencing response effort, human studies regularly constrain all response options to a single screen (e.g., Cox et al, 2019). In contrast, response options in studies with laboratory animals, in which little control responding is typical (e.g., Craig & Shahan, 2016; Shvarts et al, 2020), are considerably more spatially distributed. Additional research examining response effort could provide further insight into the role of reinforcement and generalization processes that could be integrated into theoretical accounts of resurgence.…”
Section: Discussionmentioning
confidence: 98%
“…During testing for resurgence in Phase 3, reinforcement typically is withheld for both responses, resulting in a transient recovery of target responding. Resurgence was first observed in rats (Leitenberg et al, 1970) and has since been demonstrated across several species, including fish (e.g., da Silva et al, 2014; Kuroda et al, 2017a, b), mice (Craig et al, 2020), rats (Craig & Shahan, 2016; Winterbauer & Bouton, 2010, 2011), pigeons (e.g., Liddon et al, 2017; Shvarts et al, 2020), monkeys (Mulick et al, 1976), and humans (Podlesnik et al, 2020; see Kestner & Peterson, 2017, for a review).…”
mentioning
confidence: 97%
“…However, research on the resurgence of inappropriate mealtime behavior is limited, and no analogous resurgence‐mitigation procedures have been investigated. Researchers have evaluated the utility of resurgence‐mitigation techniques for other behavior with humans and nonhuman animals, including: (a) using discriminative stimuli to signal extinction and reinforcement (Craig et al, 2017; Fisher et al, 2020; Fuhrman et al, 2016; Shvarts et al, 2020; Trask, 2019), (b) conducting treatment in unique contexts (e.g., Suess et al, 2020), and (c) teaching multiple alternative behaviors (e.g., Lambert et al, 2015). It is currently unclear to what extent these procedures may prevent resurgence of inappropriate mealtime behavior.…”
Section: Discussionmentioning
confidence: 99%